A sodium electric precursor and its preparation method and application
The high-entropy superlattice sodium-electric precursor is prepared by step-by-step co-precipitation method, which solves the problem of rapid capacity and voltage attenuation of the positive electrode material of sodium ion battery during charging and discharging, and achieves the effect of improving capacity retention and cycling performance.
Patent Information
- Application Number
- CN202310887559.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing sodium ion battery positive electrode materials have rapid capacity and voltage attenuation during charging and discharging, which affects its practical application.
Through the step-by-step co-precipitation method, doping raw materials are added reasonably in steps to prepare high-entropy superlattice sodium-electric precursor, and use its unique layered structure to improve the sodium ion deintercalation ability.
While reducing material costs, the capacity retention and cycling performance of the precursor are improved, and capacity and voltage attenuation problems are reduced.
Smart Images

Figure BDA0004346775460000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a sodium battery precursor and a preparation method and application thereof. Background Art
[0002] In the current situation of energy shortage, it is particularly important to develop new energy storage batteries such as lithium-ion batteries and sodium-ion batteries in a healthy and orderly manner, accompanied by the country's increasing requirements for the energy density of power batteries and the urgent hope that sodium-ion batteries will enter the market earlier to alleviate energy storage pressure. At present, the energy density of sodium-ion batteries is relatively low. Although layered oxide positive electrode materials have a high theoretical capacity, increasing the charging cut-off voltage will bring about problems such as metal dissolution and electrolyte decomposition. Therefore, it is necessary to study methods that can exert more capacity, effectively inhibit electrolyte decomposition, and reduce metal dissolution within the existing voltage range.
[0003] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low raw material costs and large reserves, and have great advantages in chemical energy storage, low-speed electric vehicles, base station construction, etc.
[0004] CN113644268A discloses a sodium ion battery layered positive electrode material and a preparation method thereof, wherein a sodium source material and an M source material are ball-milled and mixed under the protection of an inert gas to form a powder, and then calcined at a high temperature to form a Na x The MO2 layered material is then ground into a composite powder, and the composite powder is stirred and mixed with a doping coating salt solution under heating until the solvent is completely volatilized to obtain a coated doped powder, and the obtained coated doped powder is calcined again and cooled to obtain a sodium ion battery layered positive electrode material.
[0005] CN115207352A discloses a sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery. The sodium ion battery positive electrode material is a layered structure, and the sodium ion battery positive electrode material is co-doped with a doped metal element and a sulfur element.
[0006] The layered sodium ion battery positive electrode material prepared by the above scheme will cause the capacity and voltage to decay rapidly during the charge and discharge process due to its layered structure, which affects its application in practice. Summary of the invention
[0007] The purpose of the present invention is to provide a sodium electric precursor and a preparation method and application thereof. The present invention can prepare a high entropy superlattice sodium electric precursor by a step-by-step co-precipitation method and rationally adding doping raw materials in steps. The sodium electric precursor can reduce material costs while improving the sodium ion deintercalation ability of the precursor due to its unique layered structure, thereby improving the capacity retention rate and cycle performance of the material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a sodium electrode precursor, the method comprising the following steps:
[0010] (1) mixing a nickel salt, a manganese salt and an iron salt with a solvent to obtain a solution A, mixing a copper salt, a complexing agent and a solvent to obtain a solution B, and mixing one or more of a lithium salt, a zinc salt, a titanium salt or a magnesium salt with a solvent to obtain a solution C;
[0011] (2) injecting alkali solution, ammonia water and solution A into the bottom liquid in parallel to perform a one-step co-precipitation reaction, and injecting ammonia water, alkali solution and solution B into the bottom liquid in parallel to perform a two-step co-precipitation reaction;
[0012] (3) Injecting the precipitant solution and solution C in parallel to carry out a three-step co-precipitation reaction to obtain the sodium electrode precursor.
[0013] The method of the present invention can prepare a high entropy oxide precursor by controlling the co-precipitation sequence of the base material and various doping raw materials. The high entropy oxide precursor has the characteristics of shared crystallization sites, can stabilize the structure, improve the cycle performance, and reduce the problems of capacity and voltage attenuation.
[0014] In a preferred embodiment, if the capacity performance of the material is required to be high, a lithium salt is added to solution C; if the cycle performance of the material is required to be high, a titanium salt is added to solution C.
[0015] Preferably, the nickel salt, manganese salt, iron salt, copper salt, zinc salt, titanium salt or magnesium salt in step (1) comprises sulfate, nitrate or chloride.
[0016] Preferably, the lithium source comprises lithium sulfate.
[0017] Preferably, the complexing agent includes any one of ammonia water, acetic acid, sodium citrate or ethylenediamine, or a combination of at least two thereof.
[0018] Preferably, the mass concentration of the complexing agent in the solution B is 2-5 g / L, for example, 2 g / L, 2.5 g / L, 3 g / L, 4 g / L or 5 g / L.
[0019] Preferably, the total metal molar concentration of the solution A is 1.6 to 2.4 mol / L, for example, 1.6 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L or 2.4 mol / L.
[0020] Preferably, the base liquid in step (2) comprises ammonia water and alkali solution.
[0021] Preferably, the pH of the base solution is 9-13, for example, 9, 10, 11, 12 or 13.
[0022] Preferably, the ammonia concentration in the base solution is 1-10 g / L, for example, 1 g / L, 2 g / L, 5 g / L, 8 g / L or 10 g / L.
[0023] Preferably, the temperature of the base liquid is 40-100°C, for example, 40°C, 50°C, 60°C, 80°C or 100°C.
[0024] Preferably, the concentration of the alkali solution in step (2) is 9 to 12 mol / L, for example, 9 mol / L, 9.5 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.
[0025] Preferably, the concentration of the ammonia water is 7 to 10 mol / L, for example, 7 mol / L, 7.5 mol / L, 8 mol / L, 8.5 mol / L, 9 mol / L or 10 mol / L.
[0026] Preferably, the endpoint of the one-step coprecipitation reaction is that the particle size a of the particles in the system is 3 to 12 μm, for example, 3 μm, 6 μm, 8 μm, 10 μm or 12 μm.
[0027] Preferably, after the two-step coprecipitation reaction in step (2), the particle size in the system is b, ba = 0.8 to 3 μm, for example: 0.8 μm, 1 μm, 1.5 μm, 2 μm or 3 μm, etc.
[0028] Preferably, the solute of the precipitant solution in step (3) includes sodium hydroxide and / or potassium hydroxide.
[0029] Preferably, the concentration of the precipitant solution is 0.8-1.2 mol / L, for example, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L or 1.2 mol / L.
[0030] Preferably, the three-step co-precipitation time in step (3) is 3 to 12 hours, for example: 3 hours, 4 hours, 5 hours, 8 hours or 12 hours.
[0031] Preferably, after the three-step coprecipitation reaction is completed, the particle size of the particles in the system is c, cb = 0.3-0.8 μm, for example: 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm or 0.8 μm, etc.
[0032] Preferably, inert gas is introduced during the one-step co-precipitation reaction, the two-step co-precipitation reaction and the three-step co-precipitation reaction.
[0033] Preferably, the one-step coprecipitation reaction, the two-step coprecipitation reaction and the three-step coprecipitation reaction are performed at a temperature of 40 to 100° C., for example, 40° C., 50° C., 60° C., 80° C. or 100° C., etc.
[0034] Preferably, the stirring speed of the one-step co-precipitation reaction, the two-step co-precipitation reaction and the three-step co-precipitation reaction is 200-500 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 400 rpm or 500 rpm.
[0035] In a second aspect, the present invention provides a sodium electric precursor, which is prepared by the method described in the first aspect, and the chemical formula of the sodium electric precursor is Ni a Fe b Cu c Mn d Li e Zn x Ti y Mg z (OH)2, (a+b+c+d+e+x+y+z=1, and 0.05 <a<0.4,0.05<b<0.4,0.05<c<0.4,0.05<d<0.4,e<0.11,x<0.11,y<0.11,z<0.11)。
[0036] In the sodium electric precursor of the present invention, the cost is reduced by introducing low-priced metals such as copper and iron; zinc, titanium or magnesium are doped, and the sodium interlayer spacing is increased to make sodium ions easier to deintercalate and enhance the rate performance.
[0037] In a third aspect, the present invention provides a positive electrode material, which is prepared by mixed sintering of the sodium electrode precursor and a sodium source as described in the second aspect.
[0038] In a fourth aspect, the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the positive electrode material as described in the third aspect.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention adopts a step-by-step co-precipitation method to reasonably add doping raw materials in steps to prepare a high-entropy superlattice sodium electric precursor. The sodium electric precursor can reduce material costs while improving the sodium ion deintercalation ability of the precursor due to its unique layered structure, thereby improving the capacity retention rate and cycle performance of the material. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0042] Example 1
[0043] This embodiment provides a sodium battery precursor, and the preparation method of the sodium battery precursor is as follows:
[0044] (1) preparing a sulfate solution containing nickel ions, iron ions and manganese ions with a total ion concentration of 2 mol / L, wherein the molar ratio of Ni:Fe:Mn is 1:1:1, to obtain a mixed solution A; preparing a sulfate solution containing a copper ion concentration of 2 mol / L, adding ammonia water (ammonia concentration is maintained at 3 g / L), to obtain a mixed solution B; preparing a sulfate solution C with a titanium ion concentration of 2 mol / L; preparing a 10 mol / L alkaline solution; and preparing an 8 mol / L ammonia solution;
[0045] (2) preparing a base solution with a pH of 11 and an ammonia concentration of 5 g / L, heating to 60° C., controlling the stirring speed to 300 rpm, continuously introducing an inert gas, introducing an alkali solution, an aqueous ammonia solution and a solution A, and after the particle size grows to a target particle size D50 of 9 μm, injecting an aqueous ammonia solution, an alkali solution and a solution B in parallel, and the particle size grows to a target particle size D50 of 9.42 μm;
[0046] (3) Injecting the precipitant solution, ammonia water and solution C in parallel until the particle size D50 is 9.55 μm to obtain the sodium electric precursor, the chemical formula of which is Ni 0.20 Fe 0.28 Mn 0.37 Cu 0.10 Ti 0.05 (OH)2.
[0047] Example 2
[0048] This embodiment provides a sodium battery precursor, and the preparation method of the sodium battery precursor is as follows:
[0049] (1) preparing a sulfate solution containing nickel ions, iron ions and manganese ions with a total ion concentration of 2 mol / L, wherein the molar ratio of Ni:Fe:Mn is 1:1:1, to obtain a mixed solution A; preparing a sulfate solution containing a copper ion concentration of 2.3 mol / L, adding ammonia water (ammonia concentration is maintained at 2-5 g / L), to obtain a mixed solution B; preparing a sulfate solution C with a lithium ion concentration of 2 mol / L; preparing a 9.8 mol / L alkaline solution; and preparing an 8.2 mol / L ammonia solution;
[0050] (2) preparing a base solution with a pH of 11.2 and an ammonia concentration of 5.3 g / L, heating to 65° C., controlling the stirring speed to 350 rpm, continuously introducing an inert gas, introducing an alkali solution, an aqueous ammonia solution and a solution A, and after the particle size grows to a target particle size D50 of 8 μm, injecting an aqueous ammonia solution, an alkali solution and a solution B in parallel, and the particle size grows to a target particle size D50 of 8.45 μm;
[0051] (3) Injecting the precipitant solution, ammonia water and solution C in parallel until the particle size D50 is 8.48 μm to obtain the sodium electric precursor, the chemical formula of which is Ni 0.24 Fe 0.30 Mn 0.32 Cu 0.13 Li 0.1 (OH)2.
[0052] Comparative Example 1
[0053] The only difference between this comparative example and Example 1 is that various raw material solutions are introduced simultaneously for coprecipitation reaction, and other conditions and parameters are exactly the same as those in Example 1.
[0054] Comparative Example 2
[0055] The only difference between this comparative example and Example 1 is that no copper source is added, and other conditions and parameters are exactly the same as those in Example 1.
[0056] Comparative Example 3
[0057] The only difference between this comparative example and Example 1 is that no titanium source is added, and other conditions and parameters are exactly the same as those in Example 1.
[0058] Comparative Example 4
[0059] The only difference between this comparative example and Example 1 is that no copper source and titanium source are added, and other conditions and parameters are exactly the same as those in Example 1.
[0060] Comparative Example 5
[0061] The only difference between this comparative example and Example 1 is that the titanium source is added first and then the copper source is added. Other conditions and parameters are exactly the same as those in Example 1.
[0062] Performance Test:
[0063] The precursor obtained in the embodiment and the comparative example was pre-sintered at 400°C for 5 hours, then uniformly mixed with Na2CO3 powder according to the element ratio, and calcined in an air atmosphere at 800°C for 12 hours to obtain a sodium ion positive electrode material. The electrode material, acetylene black, and polyvinylidene fluoride were dripped into N-methyl-2-pyridine alkanone in a mass ratio of 8:1:1 to prepare a solution, which was then evenly applied on an aluminum foil, dried, and stamped into a thin sheet. The battery pole piece, single sodium sheet, glass fiber diaphragm, electrolyte (NaClO4) gasket, shrapnel, and battery shell were assembled into a button battery in an Ar gas glove box, and the battery was subjected to a performance test. The test results are shown in Table 1:
[0064] Table 1
[0065]
[0066] As can be seen from Table 1, from Examples 1-2, the battery made of the sodium battery precursor of the present invention not only reduces the cost while ensuring the discharge capacity of 0.2C, 0.5C and 1C, but also greatly improves the cycle performance. The capacity performance of the material can be improved by replacing the titanium salt with a lithium salt, but the cycle performance also decreases.
[0067] By comparing Example 1 with Comparative Example 1, it can be seen that the method of the present invention prepares a layered sodium battery precursor by a step-by-step co-precipitation method. The precursor reduces the problem of capacity and voltage attenuation due to its unique layered structure doped with multiple elements.
[0068] From the comparison between Example 1 and Comparative Example 2, it can be seen that the doping of zinc, titanium or magnesium in the present invention can increase the sodium interlayer spacing, make sodium ions easier to deintercalate, and enhance the rate performance.
[0069] From the comparison between Example 1 and Comparative Example 3, it can be seen that the introduction of copper, a cheap metal, in the present invention reduces the cost without having a significant impact on the electrical properties of the material, and is suitable for large-scale production.
[0070] From the comparison between Example 1 and Comparative Example 4, it can be seen that the capacity and voltage are improved by doping lithium into the sodium battery precursor in the present invention.
[0071] By comparing Example 1 and Comparative Examples 5-6, it can be seen that the method of the present invention can prepare a sodium battery precursor by controlling the co-precipitation order of the base material and various doping raw materials. The precursor has the characteristics of shared crystallization sites, can stabilize the structure, and improve the cycle performance.
[0072] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a sodium electrode precursor, characterized in that: The preparation method comprises the following steps: (1) mixing a nickel salt, a manganese salt and an iron salt with a solvent to obtain a solution A, mixing a copper salt, a complexing agent and a solvent to obtain a solution B, and mixing one or more of a zinc salt, a titanium salt or a magnesium salt, a lithium salt and a solvent to obtain a solution C; (2) injecting alkali solution, ammonia water and solution A into the bottom liquid in parallel to perform a one-step co-precipitation reaction, and injecting ammonia water, alkali solution and solution B into the bottom liquid in parallel to perform a two-step co-precipitation reaction; (3) injecting the precipitant solution and solution C in parallel to perform a three-step co-precipitation reaction to obtain the sodium electrode precursor; The endpoint of the one-step coprecipitation reaction in step (2) is that the particle size in the system is a, and a is 3 to 12 μm; After the two-step coprecipitation reaction in step (2), the particle size in the system is b, ba = 0.8-3 μm; After the three-step coprecipitation reaction in step (3) is completed, the particle size of the particles in the system is c, cb = 0.3-0.8 μm; The structure of the sodium-electric precursor includes a high entropy superlattice structure; The sodium electrolyte precursors have shared crystallographic sites.
2. The preparation method according to claim 1, characterized in that The nickel salt, manganese salt, iron salt, copper salt, zinc salt, titanium salt or magnesium salt in step (1) includes sulfate, nitrate or chloride.
3. The preparation method according to claim 1, characterized in that: The lithium salt in step (1) includes lithium sulfate.
4. The preparation method according to claim 1, characterized in that: The complexing agent in step (1) includes any one of ammonia water, acetic acid, sodium citrate or ethylenediamine, or a combination of at least two of them.
5. The preparation method according to claim 1, characterized in that: The mass concentration of the complexing agent in the solution B in step (1) is 2-5 g / L.
6. The preparation method according to claim 1, characterized in that: The total metal molar concentration of the solution A in step (1) is 1.6 to 2.4 mol / L.
7. The preparation method according to claim 1, characterized in that: The base liquid in step (2) includes ammonia water and alkali solution.
8. The preparation method according to claim 1, characterized in that: The pH of the base solution in step (2) is 9-13.
9. The preparation method according to claim 1, characterized in that: The ammonia concentration in the base liquid in step (2) is 1 to 10 g / L.
10. The preparation method according to claim 1, characterized in that: The temperature of the base liquid in step (2) is 40-100°C.
11. The preparation method according to claim 1, characterized in that: The concentration of the alkali solution in step (2) is 9 to 12 mol / L.
12. The preparation method according to claim 1, characterized in that: The concentration of the ammonia water in step (2) is 7 to 10 mol / L.
13. The preparation method according to claim 1, characterized in that: The solute of the precipitant solution in step (3) includes sodium hydroxide and / or potassium hydroxide.
14. The preparation method according to claim 1, characterized in that: The concentration of the precipitant solution in step (3) is 0.8 to 1.8 mol / L.
15. The preparation method according to claim 1, characterized in that: The time for the three-step co-precipitation in step (3) is 3 to 12 hours.
16. The preparation method according to claim 1, characterized in that: Inert gas is introduced during the one-step co-precipitation reaction, the two-step co-precipitation reaction and the three-step co-precipitation reaction.
17. The preparation method according to claim 1, characterized in that: The temperature of the one-step coprecipitation reaction, the two-step coprecipitation reaction and the three-step coprecipitation reaction is 40-100°C.
18. The preparation method according to claim 1, characterized in that: The stirring speed of the one-step co-precipitation reaction, the two-step co-precipitation reaction and the three-step co-precipitation reaction is 200-500 rpm.
19. A sodium electrode precursor, characterized in that: The sodium battery precursor is prepared by the method according to any one of claims 1 to 18, and the chemical formula of the sodium battery precursor is Ni a Fe b Cu c Mn d Li e Zn x Ti y Mg z (OH)2, a+b+c+d+e+x+y+z=1, and 0.05 <a<0.4,0.05<b<0.4,0.05<c<0.4,0.05<d<0.4,e<0.11,x<0.11,y<0.11,z<0.11。 20. A positive electrode material, characterized in that The positive electrode material is obtained by mixed sintering of the sodium electrode precursor and the sodium source as described in claim 19.
21. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode material as claimed in claim 20.
Citation Information
Patent Citations
Layered positive electrode material of sodium-ion battery and preparation of layered positive electrode material
CN113644268A
Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery
CN115207352A
Spherical-like sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
CN115000399A
Sodium positive electrode precursor material and preparation method and application thereof
CN115732674A